Neural indicators of interpersonal anger as cause and consequence of combat training stress symptoms. Issue 9 (5th January 2017) - Gilam, G.; Lin, T.; Fruchter, E.; Hendler, T.
Abstract : Background: Angry outbursts are an important feature of various stress-related disorders, and commonly lead to aggression towards other people. Findings regarding interpersonal anger have linked the ventromedial prefrontal cortex (vmPFC) to anger regulation and the locus coeruleus (LC) to aggression. Both regions were previously associated with traumatic and chronic stress symptoms, yet it is unclear if their functionality represents a consequence of, or possibly also a cause for, stress symptoms. Here we investigated the relationship between the neural trajectory of these indicators of anger and the development and manifestation of stress symptoms. Method: A total of 46 males (29 soldiers, 17 civilians) participated in a prospective functional magnetic resonance imaging experiment in which they played a modified interpersonal anger-provoking Ultimatum Game (UG) at two-points. Soldiers were tested at the beginning and end of combat training, while civilians were tested at the beginning and end of civil service. We assumed that combat training would induce chronic stress and result in increased stress symptoms. Results: Soldiers showed an increase in stress symptoms following combat training while civilians showed no such change following civil service. All participants were angered by the modified UG irrespective of time point. Higher post-combat training stress symptoms were associated with lower pre-combat training vmPFC activation and with higher activation increase in the LC between pre- and post-combat training. Conclusions: Results suggest that during anger-provoking social interactions, flawed vmPFC functionality may serve as a causal risk factor for the development of stress symptoms, and heightened reactivity of the LC possibly reflects a consequence of stress-inducing combat training. These findings provide potential neural targets for therapeutic intervention and inoculation for stress-related psychopathological manifestations of anger.